Zero-Waste Management and Sustainable Consumption: A Comprehensive Bibliometric Mapping Analysis - Escobar-Farfan, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The growth of waste generation is a global problem. Developing effective waste management methods is challenging for companies and the government. This research aims to provide a global perspective regarding scientific research on zero-waste management and sustainable consumption by identifying years of evolution, the most relevant and influential keywords, articles, journals, universities, countries, and authors. This research examines 2534 publications from the Web of Science Core Collection from 2011 to 2021. Numerous bibliometric indices, including the number of publications, the h-index, and citation requirements, have been used as evaluating techniques. Additionally, a relational technique has been developed through graphical maps using the VOS viewer Software. Results show a growing trend in the number of zero-waste management’s publications and citations. Regarding the h-index, the five most relevant journals are the Journal of Cleaner Production, Resources Conservation and Recycling, Waste Management, Waste Management Research, and Sustainability. The most outstanding author is Tsang Dan from Zhejiang University, and the leading university is the Chinese Academy of Science, China. Furthermore, the principal regions and continents are China—Asia, USA—America, and Italy—Europe. The most important keywords are waste management, sustainability, circular economy, and sustainable development. This article is the first quantitative study focused on contributing a complete overview of the progress of zero-waste management and sustainable consumption, providing a collaborative network of researchers for future use in generating knowledge. © 2022 by the authors.